2011
DOI: 10.1007/s11182-011-9509-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-beam epitaxy of GaAs/Si(001) structures for high-performance tandem A III B V/Si-solar energy converters on an active silicon substrate

Abstract: In the present study, a method of low-temperature atomic layer epitaxy of GaAs at the initial stage of formation of a GaAs/Si heterojunction is used for growing GaAs films with a low density of threading defects. It was shown that growth of GaAs films can take place bypassing the stage of formation of islands, provided the first monolayer of GaAs is formed by atomic layer epitaxy at low temperature (200-350°С). A regime was found for growing the GaAs/Si films with a density of threading dislocations less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Direct epitaxial growth thin films of III-V semiconductors on Si is challenging due to the high lattice mismatch between top and bottom cells which induces dislocations and introduces losses, preventing the development of highly-efficient devices. Although the introduction of buffer layers [7,8] can increase the cell efficiency, the improvement achieved with these techniques still lies below the performances obtained at Kaneka corporation.…”
Section: Introductionmentioning
confidence: 94%
“…Direct epitaxial growth thin films of III-V semiconductors on Si is challenging due to the high lattice mismatch between top and bottom cells which induces dislocations and introduces losses, preventing the development of highly-efficient devices. Although the introduction of buffer layers [7,8] can increase the cell efficiency, the improvement achieved with these techniques still lies below the performances obtained at Kaneka corporation.…”
Section: Introductionmentioning
confidence: 94%
“…The work of Lueck et al [7] in the same year demonstrated similar techniques and achieved an efficiency of 17% under AM1.5G spectrum. Work in this field continues with Putyato et al [8] developing graded buffer approaches. While these methods have made progress, the efficiencies achieved remain subject to materials quality limitations due to the fundamental problem of high defect densities, despite the use of buffers to reduce them to acceptable levels.…”
Section: Introductionmentioning
confidence: 99%
“…On Earth, many high efficiency concentrator solar cells rely on materials such as GaInNAs [12] and In0.3Ga0.7As [13] with low diffusion lengths, either due to intrinsic material quality or lattice mismatching with adjacent subcells. Similarly, in III-V-on-Si MJ tandems, lattice mismatching leads to high defect densities and low diffusion lengths in the III-V top cell [14][15][16]. All these technologies would be improved if one or more of the subcells could be thinned whilst maintaining strong photon absorption.…”
mentioning
confidence: 99%